Ethnopedagogy in the Light of the Philosophy of Science of Islamic Education - Ishak; Hasmuddin; M. Fatahuddin; M. Ilyas; Abdul Halik (Universitas Muhammadiyah Palu, 2025)
Ethnopedagogy is an educational approach that integrates local values, traditions and cultures in the teaching and learning process. It aims to make education more relevant to people's lives and strengthen learners' cultural identity. Relevance to Islamic Education In Islamic education, ethnopedagogy helps connect local cultural values with Islamic teachings. Shaping learners' Islamic character through local traditions, such as gotong royong and deliberation. Instilling spiritual and moral values in the cultural context of the community. Contributions to ethnopedagogy character building in Islamic education are increasing awareness of cultural and Islamic identity. Integrating local wisdom that is in line with Islamic principles, such as harmony with nature and manners. Strengthening Islamic character through cultural and religious role models. Implementation Challenges Indonesia's cultural diversity is complex and diverse. Lack of teacher understanding of the concept of ethnopedagogy. The dominance of the national curriculum which lacks flexibility for local content. Conflict between certain local traditions and Islamic values. Community resistance to the integration of local culture in education. Research Methods This research uses a qualitative approach and literature review, relying on observation techniques, interviews, documentation, and local culture-based data analysis in Islamic education. Conclusion Ethnopedagogy and the philosophy of science of Islamic education complement each other in shaping education that: Values cultural diversity. Build learners' identity based on Islamic values and local culture. Make education more relevant, meaningful and contextual. This approach requires policy support, teacher training, local culture-based teaching materials, and collaboration between stakeholders.